Nurturing Identity and Values: Meunasah’s Role in Acehnese Early Childhood Development - Cut Intan Meutia; Chery Julida Panjaitan; Fadhillah Wiandari (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study explores the role of Meunasah as a non-formal learning space for early childhood education in Aceh, focusing on its benefits and challenges. Meunasah, a community institution with a strong emphasis on religious education, provides young children with opportunities to engage in spiritual development, social interaction, and cultural learning. This research employs a qualitative case study approach, combining semi-structured interviews, participant observation, and document analysis to gather data from Meunasah teachers, community leaders, parents, and local education authorities. The findings reveal that Meunasah plays a vital role in fostering children's spiritual development, moral values, and social skills through communal activities and early religious instruction. These experiences contribute to children's emotional regulation, sense of identity, and social responsibility. However, the study also identifies several challenges that limit Meunasah’s effectiveness as a holistic learning environment. These include inadequate learning resources, lack of formal teacher training in early childhood pedagogy, and inconsistent parental involvement. Despite these limitations, the research highlights the potential of Meunasah to complement formal education systems by promoting a more integrated and community-based approach to early childhood development. Strengthening the role of Meunasah through curriculum development, teacher training, and collaboration with families and schools is essential to maximize its impact. Ultimately, Meunasah holds promise as a key pillar in Aceh’s early education landscape, provided that systemic support is in place.